Pengaruh Kecerdasan Emosional dengan Kenakalan Siswa - HM Adibussholeh (Indonesian Journal of Humanities and Social Sciences, 2022)
The relationship between emotional intelligence and delinquency is always framed by cause and effect. Many theories of child development explain this relationship. In this context, this study aims to see the relationship between emotional intelligence and delinquency in class XI students at SMK Negeri 1 Nganjuk. This research method is quantitative with a linear correlation approach. A correlation study is a research that involves collecting data to determine the existence of a relationship and the degree of relationship between two or more variables. In accordance with the research findings, the research hypothesis is that there is a significant relationship between emotional intelligence affecting the formation of juvenile delinquency Based on the analysis, the results obtained in this study are: (1) the emotional intelligence aspects in the high category namely 19 respondents as much as 47%. (2) The juvenile delinquency aspects in the low category, namely 20 respondents as much as 50%. (3) Correlation results show a negative relationship between emotional intelligence and juvenile delinquency with the value of the correlation coefficient -325 and p=0,000 < 0,05. This means that the higher the emotional intelligence, the lower the juvenile delinquency.